Metabarcoding of zooplankton communities of Dianchi Lake based on the mitochondrial cytochrome oxidase subunit 1 gene - Cen, Fu; Xu, Shan; Yin, Genshen; Dong, Minghua (Frontiers in Microbiology, 2024)
Freshwater lakes as an essential component of the ecosystem, provide ecological resources in addition to economic source for humans. Under recent climate change scenario, preserving the biodiversity of freshwater ecosystems is crucial. This study aimed to characterize the diversity of zooplankton communities in Dianchi Lake, located in Kunming Municipality, Yunnan Province, China, using Illumina high-throughput sequencing of the cytochrome oxidase subunit 1 (COI) gene marker. A total of 18 water samples were collected including 16 from the outer sea area of Dianchi Lake: 4 from the east (E1-4), 4 from the west (W1-4), 4 from the south (S1-4), and 4 from the north (N1-4), and: 2 from the Caohai area (C1-2) as research sites. All environmental parameters including pH, ammonium (NH 4+ ), total nitrogen (TN), total phosphorus (TP), chlorophyll a content (CHLA) were found to be insignificant (p > 0.05), except for chemical oxygen demand (COD) and transparency (T), which were found to be significant (p < 0.05). Alpha diversity indices including ACE, Chao1, Shannon and Simpson showed non-significant differences (p > 0.05), indicating no variation in the richness of zooplankton communities at different locations of Dianchi Lake.However, Principal Coordinate Analysis (PCoA) showed that most of the samples from East, West, and South groups were close to each other, showing more similarities among them, while Caohai and North group samples were distant from each other, showing more differences with other groups. Rotifera, Arthropoda, and Chordata were the top three phyla, while Keratella, Macrothrix, and Brachionus were the dominant genera. Mantel test analysis showed that COD and transparency were important environmental factors that shaped the Rotifera community structure of Dianchi Lake. In conclusion, this study provides insights on conserving the diversity of zooplankton communities in Dianchi Lake, especially by controlling COD and maintaining water transparency, in order to preserve its ecological resources and economic significance.